Neoadjuvant Therapy for Locally Advanced Esophageal Cancers - Huang, Runkai; Qiu, Zhenbin; Zheng, Chunwen; Zeng, Ruijie; Chen, Wanxian; Wang, Simeng; Li, Enmin; Xu, Yiwei (Frontiers in Oncology, 2022)
Esophageal carcinoma is one of the most aggressive malignant diseases. At present, neoadjuvant chemotherapy and neoadjuvant chemoradiotherapy are regarded as the standard modalities for the treatments of locally advanced esophageal cancers based on several landmark trials. However, the optimal regimen, radiation dose, and surgical intervals are uncertain and the rate of recurrence after neoadjuvant therapy is high. Patients receiving neoadjuvant therapy and reaching a pathological complete response have been reported to have a better survival benefit and a fewer recurrence risk than those non-pathological complete responses. Nevertheless, less than half of patients will reach a pathological complete response after neoadjuvant therapy, and the methods to evaluate the efficacy after neoadjuvant therapy accurately are limited. Immune checkpoint inhibitors have been recommended for the treatments of advanced esophageal cancers. Recently, research has been beginning to evaluate the safety and efficacy of immunotherapy combined with neoadjuvant therapy. Here, we will review and discuss the development of the neoadjuvant therapy of locally advanced esophageal cancers and unsolved clinical problems.